The change in muscarinic receptor subtypes in different brain regions of rats treated with fluoxetine or propranolol in a model of post-traumatic stress disorder - AYDIN OMAY, BANU; CABADAK, HÜLYA; GÖREN, MEHMET ZAFER (ELSEVIER SCIENCE BV, 2012)
This study shows the possible contribution of muscarinic receptors in the pathophysiology of post-traumatic stress disorder. Sprague-Dawley rats of both sexes were exposed to dirty cat litter (trauma) for 10 min and the protocol was repeated 1 week later with a trauma reminder (clean litter). The rats also received intraperitoneal fluoxetine (2.5, 5 or 10 mg/kg/day), propranolol (10 mg/kg/day) or saline for 7 days between two exposure sessions. Functional behavioral experiments were performed using elevated plus maze, following exposure to trauma reminder. Western blot analyses for M-1, M-2, M-3, M-4 and M-5 receptor proteins were employed in the homogenates of the hippocampus, the frontal cortex and the amygdaloid complex. The anxiety indices increased from 0.63 +/- 0.02 to 0.89 +/- 0.04 in rats exposed to the trauma reminder. The freezing times were also recorded as 47 +/- 6 and 133 +/- 12 s, in control and test animals respectively. Fluoxetine or propranolol treatments restored the increases in the anxiety indices and the freezing times. Female rats had higher anxiety indices compared to males. Western blot data showed increases in M-2 and M-5 expression in the frontal cortex. Expression of M-1 receptors increased and M-4 subtype decreased in the hippocampus. In the amygdaloid complex of rats, we also detected a down-regulation of M-4 receptors. Fluoxetine and propranolol only corrected the changes occurred in the frontal cortex. These results may imply that muscarinic receptors are involved in this experimental model of post-traumatic stress disorder. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Hippocampus; Amygdaloid complex; Frontal cortex; Predator scent test; Cat litter; HIPPOCAMPAL ACETYLCHOLINE-RELEASE; ANIMAL-MODEL; ANXIETY; MEMORY; LOCALIZATION; RESPONSES; NEUROTRANSMISSION; ANTIDEPRESSANTS; IDENTIFICATION; EXTINCTION